PENERAPAN KEBIJAKAN PENAL DAN NON PENAL DALAM UU NO. 6 TAHUN 2018 PADA KASUS JOKI VAKSIN DAN JOKI KARANTINA - Faqih Zuhdi Rahman, (2022)
This research have to purpose to prescriptively analyze the urgency and implementation of the realize penal and non-penal policies in the Health Quarantine Law No. 6 of 2018 in the case of vaccine jockeys and quarantine jockeys. We all know that there are many cases of violation of Health protocols and so many way how to punishment. Crime case of the law against the health quarantine law no. 6 of 2018 which is related to the infectious disease outbreak law no. 4 of 1984, the law guide whoever are a person or legal entity that hinders made mental health nationally. Currently, in the case of vaccine jockeys and quarantine jockeys in law enforcement during the COVID-19 pandemic, there are two possible ways of law enforcement through penal and non-penal way. In difficult situation like this the using law enforcement and application is something that can result in orderly and chaotic conditions in Indonesia in wipe out the decrease COVID-19 cases, therefore the author focuses on the study of the urgency and implementation of penal and non-penal policies in Law no. 6 of 2018 concerning health quarantine in the case of vaccine jockeys and quarantine jockeys. The method in this study is normative legal research by focusing on secondary and tertiary materials such as the Health Quarantine Act No. 6 of 2018 and the Law of Infectious Diseases No. 4 of 1984 and something like that as well as relevant cases regarding vaccine jockeys and quarantine jockeys. In the results of this study, it was found the need for law enforcement on violations of Health protocols in cases of vaccine jockeys and quarantine jockeys based on penal and non-penal policies, the implementation of which was adjusted to the urgency of its application so that not only fair laws and ideals could be realized but also humane and orderly society, which is preventive and not always on the action.